THE ROLE OF THE SCHOOL COMMITTEE IN IMPROVING THE QUALITY OF SCHOOLS AT SD INPRES MALEI - Faisal Faisal; Yusdin Gagaramusu; Pahriadi Pahriadi (Universitas Tadulako, 2021)
The main problem in this study is the extent to which the role of the school committee in improving the quality of schools at SD Inpres Malei, Pasangkayu Regency, West Sulawesi. The purpose of this study was to determine the role of school committees in improving school quality. The data in this study were collected through interviews/interviews and documentation studies. The results of the study indicate that the School Committee has implemented several performance indicators related to its four roles, namely as a consideration, supporter, controller, and as a mediator in an effort to improve school quality. In addition to providing input on the general school management system, the School Committee also provides input on the use of school budgets. The School Committee recommends using the budget by first maximizing the BOS funds received by the school. School Committees are not always directly involved in the policy-making process, but supervision is carried out through direct meetings with the Principal. In addition, the school also always provides a report on every policy it takes for approval. In terms of policy quality, so far the School Committee has given a good assessment of all policies taken by schools. The School Committee gives full trust to the school, so that until now it has never criticized the school's decisions.